Studi Empirik Pengambilan Keputusan Pembelian Apartemen Di Semarang - Heru Eko Prasetyo; A. Amsar; Jaluanto Sunu Punjul Tyoso (Universitas Veteran Bangun Nusantara, 2023)
The purpose of this study is to examine the influence of lifestyle, location and service quality on the process of making a decision to buy an apartment at Amartha View Semarang. An empirical approach is used in this study, collecting data from customers who live in Amartha View Semarang. The questionnaire serves as a tool that contains structured questions about lifestyle, location, service quality and purchasing decision process. The analytical method used is multiple linear regression with a sample size of 90. Decisions show lifestyle, location and quality of service give a significant positive effect on purchasing decisions. Future studies should be able to add more variables such as price, advertising innovation, demographics, taste and comparison with other household contents and increase the sample size used.